Bone tissue mineral density of pre-born infant twins and its correlations with the prenatal factors of their mothers - Tsymbal, А. (Запорізький державний медичний університет, 2022)
Objective: to determine the level of bone mineral density (BMD) in prematurely born infant twins and their correlation with prenatal factors of their mothers.
Keywords: тези доповідей